The World - System of Capitalism: Past and Present - L. Goldfrank Water (American : Sage Publications, 1979)
Contents
Part 1: Issues in thetheory and method
Part 2: The developing core in the seventeeth century
Part 3: The developing core in the twentieth century
Part 4: Incorporation and resistance
Part 5: Class struggles in the twentith-century perriphery
Keywords: Capitalism--History--Congresses; Economics; American Sociological Association